Panorama of foreign body in upper digestive tract in the population of Uttarakhand - Bansal, Chetan; Bharti, Prerana; Singh, V. P. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Foreign body aspiration is more common in children than adults because they explore the world with their hands and mouth and also have incomplete control and immature judgment. Foreign bodies in ENT are a medical emergency as their removal demands great skill due to unpredictability in the procedure and the complications associated with it. Methods: A prospective study was conducted on 40 cases of digestive tract foreign bodies in relation to age, sex, type, site, clinical presentation, extraction and complications. Results: Youngest child was 5 months old. Most predisposed age group was 0-5 years (60% of cases). Cricopharynx (24 cases) was the most common site of impaction for foreign body. In the present study toys (22.5%) were most common foreign bodies followed by coins (15%) ingestion. Conclusions: Avoid carelessness. Avoid hasty drinking, eating, talking and running with anything in the mouth. Keep the things out of reach of the children. Be particular in sleep, anesthesia, coma or delirium. Avoid putting objects into mouth.